Pengaruh Kepribadian, Pembelajaran, Kemampuan Dan Karakteristik Biografis Terhadap Komitmen Organisasi Pada Karyawan BMT UGT Sidogiri Surabaya - Imada Ulinnuha (JOURNAL OF SHARIA ECONOMICS, 2020)
There are several factors that can affect the level of employee organizational commitment. Some of these factors include personality, learning, abilities and biographical characteristics. This research used quantitative research. From the results of this test to prove the simultaneous and partial influence between personality variables, learning, abilities, and individual characteristics of organizational commitment to BMT UGT Sidogiri employees in Surabaya. For the F test that there was a simultaneous and significant influence between the variables of individual characteristics on organizational commitment to BMT UGT Sidogiri employees, which had a significance level of 0,000 <0.05 and an F count of 8.498> 2.606. For the results of the t test or partial test, that the most significant personality influenced the value of t arithmetic> t table was 3.286> 2.0129, while other variables such as learning with t value <t table was -1.814 <2.0129 showed that there was no significant effect on organizational commitment, the ability with a t value <t table that was 1.978 <2.0129 indicated that there was a partial but not significant effect, and biographical characteristics with a t value <t table that was 1.102 <2.0129 showed that there was a partial but not significant effect on organizational commitment in BMT UGT Sidogiri employees in Surabaya. The influence of personality variables, learning, ability and biographical characteristics on organizational commitment in BMT UGT Sidogiri employees was expected for the institution to pay attention to the organizational commitment of employees. Keyword: employee’s personality, employee’s learning, employee’s ability, employee’s biographical characteristics, organizational commitment.